Constructing atomically-dispersed Mn on ZIF-derived nitrogen-doped carbon for boosting oxygen reduction - Deng, Yaoyao; Pang, Jiazheng; Ge, Wenzheng; Zhang, Minxi; Zhang, Wentao; Zhang, Wei; Xiang, Mei; Zhou, Quanfa; Bai, Jirong (Frontiers in Chemistry, 2022)
Exploring durable and highly-active non-noble-metal nanomaterials to supersede Pt-based nanomaterials is an effective way, which can reduce the cost and boost the catalytic efficiency of oxygen reduction reaction (ORR). Herein, we constructed atomically-dispersed Mn atoms on the ZIF-derived nitrogen-doped carbon frameworks (Mn-Nx/NC) by stepwise pyrolysis. The Mn-Nx/NC relative to pure nitrogen-doped carbon (NC) exhibited superior electrocatalytic activity with a higher half-wave potential (E1/2 = 0.88 V) and a modest Tafel slope (90 mV dec-1) toward ORR. The enhanced ORR performance of Mn-Nx/NC may be attributed to the existence of Mn-Nx active sites, which can more easily adsorb intermediates, promoting the efficiency of ORR. This work provides a facile route to synthesize single-atom catalysts for ORR.